Music listening tactics on streaming services: a multi-sited digital ethnography (PerCursos, 2024)
Due to the centrality streaming services in the digital music economy, the article observes the music listening practices that operate through the digital platforms. Adopting a multi-sited digital ethnography, we followed listeners located in different countries. Using the audioscrobbler tool and maintaining conversations whether by email or WhatsApp, we sought to understand how individuals use the interface of streaming services to listen to music, as well as how they deal with automatic music recommendation systems in in their daily life. The goal is to find out if individuals still create what are labeled here as music listening tactics ven in the face of automatic recommendation systems.
Keywords: strategies and tactics; music listening practices; streaming services; automatic music recommendation systems; multi-sited ethnography